A Computer Program Development for a Garment's Pre-Cost Account Calculation in Apparel Industry - EREN, EMİNE RÜMEYSA (EGE UNIV, 2019)
The minimum difference between the pre-cost and actual cost in the apparel sector is very important for the enterprises to sustain their profitability. The fact that the estimated unit cost calculation requirement is very frequent and continuous in an environment where competition is increasing rapidly increases the workload of enterprises. In order to be able to take orders, companies must calculate the pre-cost estimation as close as possible to the actual cost. At this stage, companies encounter problems in fabric cost estimation which has the largest share especially in product cost. In this study, a computer program, which will be used in both weaving and knit top clothing group, has been formed in order to lighten the loads of apparel companies on the pre-unit cost calculation. The interface of the computer program is formed in C # programming language using Visual Studio and DevExpress programs. The most important attribute of this program is that, it can calculate the product unit fabric quantity and marker efficiency by using only the product measurement table without the need of a model design department. In order to achieve this, equations were created in the area of calculation of product pattern areas. The program incorporates all cost components in a progressive calculation and consequently presents a product pre-cost report. The computer program was performed in two companies that work in the field of export of woven and knit top apparel in Izmir. The data obtained from the program were compared with the actual data from the companies.
Keywords: Product cost in apparel; unit cost; preliminary cost; computerized cost calculation; cost of fabric; amount of unit fabric